Throughput Modeling and Validation of MIMO Terminals With Adaptive MCS and Layers - Wei, Jianchuan; Huang, Xiaoyu; Qian, Bingyi; Zhang, Liuyang; Zhang, Aofang; Wei, Kunpeng; Chen, Xiaoming (IEEE transactions on instrumentation and measurement, 2024)
Throughput modeling in multiple-input multiple-output (MIMO) systems have attracted widespread attentions. Nevertheless, the current throughput model is confined to the case of fixed data streams (layers) and modulation and coding scheme (MCS). In the proposed study, we expand the conventional throughput model based on the transmit selection diversity and threshold translation mapping techniques to enable its use in systems where the MCS and layers are adaptively modified depending on channel quality. Excellent agreement between the simulation and measurement results confirms the effectiveness and accuracy of the suggested throughput model.